Cleansing my abuse: A reparative response model of perpetrating abusive supervisor behavior - Liao, Zhenyu; Yam, Kai Chi; Johnson, Russell E; Liu, Wu; Song, Zhaoli (Journal of applied psychology, 2018)
Research on abusive supervision has predominantly focused on the consequences for victims while overlooking how leaders respond to their own abusive behavior. Drawing from the literature on moral cleansing, we posit that supervisors who engage in abusive behavior may paradoxically engage in more constructive leadership behaviors subsequently as a result of feeling guilty and perceiving loss of moral credits. Results from two experience sampling studies show that, within leaders on a daily basis, perpetrating abusive supervisor behavior led to an increase in experienced guilt and perceived loss of moral credits, which in turn motivated leaders to engage in more constructive person-oriented (consideration) and task-oriented (initiating structure) leadership behaviors. In addition, leader moral attentiveness and moral courage strengthen these indirect effects by amplifying leaders' awareness of their immoral behavior and their willingness and determination to make reparations for such behavior. Our research contributes to the theoretical understanding of leaders' responses toward their own abusive supervisor behavior and provides insights into how and when destructive leadership behaviors may, paradoxically, trigger more constructive behaviors. (PsycINFO Database Record